Community Advocacy and Quality Education in Kwara State Senior Secondary Schools: The Nexus - Fashiku, Christopher Oluwatoyin; Abogunrin, Kehinde Olayemi; Yusuf, Abubakar Abiola; Fashiku, Bunmi Comfort (International Journal of Educational Management, 2021)
The study was carried out to investigate the relationship between community advocacyand quality education in kwara state senior secondary schools, Nigeria. Descriptive Survey research design was used in the study. Population of the study comprised all the 5,190 members of the Community Advocacy Committee including principals from 346 public senior secondary schools in Kwara State. The sample of the study comprised 336 respondents from 48 public senior secondary schools using multi-stage sampling procedure. Two self-designed validated research instruments were used, with reliability index of 0.78 and trustworthiness of the interview ensured. Data collected were analysed using percentage scores and Pearson's product. Moment correlationl statistics. The results showed that availability of funds (63%), people's awareness about the roles of community advocacy committee (64%),good school-community relationship (69%) among otherswere factors that facilitated the functions of the committees in ensuring quality education in Kwara State senior secondary schools. Also, there was a significantrelationship betweencommunity advocacy and quality education in Kwara state public secondary schools (r= cal. 0.573>t= 0.195).The study concluded that positive iinvolvement of the community tab. Member in school governance enhanced quality education in the schools. It was recommended that: Government should ensure operational policy and encourage non-committed members through good school-community relationship to promote quality education.